THE PHYTOREMEDIATION POTENTIAL OF LOTUS: DEGRADATION BOD AND COD LIQUID COFFEE WASTE - Maria Ulfah; Dian Asmaranty; Atip Nurwahyunani (BIOEDUKASI, 2021)
Liquid coffee waste has the main component in the form of organic matter which is very resistant to increasing pollutant loads. Preliminary research results show that the level of pollution exceeds the quality standard with the test results of 23 ppm BOD and 72 ppm COD, so we need a way to prevent pollution. One way that can be used is the phytoremediation method by utilizing plants as pollutant degrading agents. The purpose of this research was to determine the effectiveness of lotus in degradation of BOD and COD of liquid coffee waste. The research method used an experimental method with a Completely Randomized Design consisting of four variations of lotus biomass 0 g, 25 g, 50 g, and 75 g with three replications within 6 days. The results showed a degradation of BOD and COD levels varied. The most effective treatment for lotus phytoremediation on day 3 was P3 with a biomass of 75 g resulting in a degradation of BOD and COD reaching 72% and 71% which met the PP RI No. 82/2001 with a maximum limit of 3 ppm BOD and 25 ppm COD. The results of the homogeneity of variance test showed that the four treatments had homogeneous variance and analysis of variance showed that F count > F table 5% (4.07) and > F table 1% (7.59). These results indicate that lotus is effectively used as phytoremediation of liquid coffee waste. The conclusion of this research is that lotus is effective in BOD and COD degradation of liquid coffee waste.